Economic impact of climate change on Malaysian rice production - Vaghefi, Seyedeh Negin (2013)
Climate change poses challenges for all sectors of an economy, particularly those dependent on natural resources such as agriculture. Studies have shown that overall agricultural productivity in low latitudes are likely to decline with the effect of climate change. This has implications for world food security, as most developing countries, including Malaysia, are located in lower latitude regions. This will subsequently affect farm income, self-sufficiency level and food security. Rice production in Malaysia, as in other parts of the world, is extremely vulnerable to weather changes and extreme conditions such as drought and flooding. Such situations forced Malaysia to start and maintain a protectionist regime with respect to its rice industry to better ensure food security for the country. This study attempts to investigate the economic impact of climate change on the Malaysian rice industry, a strategic crop that largely determines the Malaysian food security. The study involves estimating the potential impact of temperature and rainfall changes on rice yields in the major rice granary areas until 2030, and policy simulation under the present and alternative policy scenarios on the rice industry. This study employed a Crop Simulation Model (DSSAT) to predict the rice production in the eight granary areas until 2030, based on projected weather data. The DSSAT model can simulate growth, development, and yield of a crop growing on a uniform area of land under recommended or simulated management. It needs the minimum data sets including weather data, soil data, and crop management data. The projected climate change over Peninsular Malaysia showed an increasing trend for maximum, minimum temperatures and changes in rainfall pattern. Increase in temperature and variations in rainfall pattern over the growing period were found to affect the rice yield. Results show that during the main growing season, a yearly increase in temperature by 0.05°C and rainfall by 0.11mm can be expected to reduce the rice yield by 12% until the year 2030. During the off season, a yearly increase of maximum and minimum temperatures by 0.15°C and 0.08°C,respectively, and a reduction in rainfall by 0.19mm would reduce the rice yield by 31.3% over the next 18 years. These results indicated that rice yield would be more negatively affected by the climate change during off season rather than main season. The system dynamics simulation model then used to assess the effect of predicted yield on self sufficiency level and farmers’ gross income of the country until 2013. It is an approach for analysing and solving complex problems, and focuses mostly on policy analysis and design. Based on the system dynamics’ results, the reduction in rice yield was expected to reduce farmers’ gross income and the rice self sufficiency level of the country. The study suggested three different policy scenarios to overcome these adverse effects. Under Scenario 1, a doubling of the government’s fertilizer subsidy from the year 2013 to 2030 was able to increase the rice yield, SSL, and farmers’ gross income about 3‒4%, 0.3‒5.6%, and 8.3‒12.7%, respectively. Based on Scenario 2, if the government increases the price support by 10% during the 2013 to 2030 time period, the farmers’ income will also increase by 1.7% per year. Under Scenario 3, Malaysia may be able to sustain the 70% SSL target until 2020, if the government open about 51,565 ha of new land area for rice fields. Malaysia also can maintain this level of self sufficiency until 2030, if the area planted increase to 154,000 ha. The overall policy implication is that the Malaysian rice industry cannot be sustained if government takes no action to change its current policies.